Two-dimensional layered MXene nanosheet and preparation method thereof

Through homogeneous treatment and rapid annealing treatment, the problems of many defects, irregular shapes and poor stability in the preparation of MXene nanosheets are solved, and the efficient and environmentally friendly preparation of MXene nanosheets are achieved. The product has uniform thickness, regular shape and high stability.

CN119503806APending Publication Date: 2025-02-25CHANGCHUN UNIV OF TECH

Patent Information

Application Number
CN202411488553.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the existing MXene nanosheet preparation method, the product has problems such as many defects, irregular shapes and poor stability.

Method used

The multi-layer MXene powder obtained by etching was used as the precursor, and homogenized by a homogenizer, followed by rapid annealing to remove functional groups on the surface of the MXene, and MXene nanosheets with regular structural and few defects were prepared.

Benefits of technology

The MXene nanosheets are uniform in thickness, high stability, regular shape and few defects, avoid oxidation problems, and the process is environmentally friendly and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503806A_ABST
    Figure CN119503806A_ABST
Patent Text Reader

Abstract

The invention discloses a two-dimensional layered MXene nanosheet and a preparation method thereof, and belongs to the technical field of MXene preparation. The method comprises the following steps: (1) etching an MAX phase powder material by using hydrofluoric acid to obtain an etched MAX phase; (2) centrifuging and drying the etched MAX phase to obtain multi-layer MXene powder; (3) carrying out homogenization treatment on the multiple layers of MXene powder; and (4) carrying out rapid annealing treatment on the powder obtained after homogenization treatment to remove functional groups on the surface of MXene so as to prepare the MXene nanosheet with a regular structure and few defects. The method effectively avoids the oxidation problem of MXene, realizes feasible preparation with uniform thickness, stability, regular shape and fewer defects, and has the advantage of replacing an organic reagent intercalation preparation method to become a mainstream preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of MXene preparation, and in particular to a two-dimensional layered MXene nanosheet and a preparation method thereof. Background Art

[0002] MXene is a two-dimensional material. It is a research result of Drexel University in the United States. Unlike traditional batteries, this material provides more channels for the movement of ions, greatly increasing the speed of ion movement. Two-dimensional materials are sheet materials composed of a single layer or a few layers of atoms with a thickness of nanometers. Its biggest feature is that the atoms in the layer are connected in the form of ionic bonds or covalent bonds, and the layers are connected by weaker van der Waals forces, thus showing unique physical and chemical properties.

[0003] With the deepening of research, graphene-like materials such as transition metal sulfides (TMDs), black phosphorus (BP) and hexagonal boron nitride (h-BN) have been discovered one after another. Two-dimensional materials have broad application prospects in flexible electronic devices, photovoltaic devices, fuel cells, supercapacitors, electrocatalysis and friction lubrication due to their excellent conductivity, optical properties, chemical stability and high specific surface area. Ti3C2Tx is the earliest member of the MXenes family, and the research on Ti3C2Tx is the most in-depth. Ti3C2Tx has been widely used in many fields such as batteries and supercapacitors, photocatalysis, electromagnetic shielding, water purification, sensors and biomedicine. However, compared with other two-dimensional materials, the research on Ti3C2Tx in the field of friction reduction and lubrication is still in its infancy. The preparation of MXene nanosheets usually involves mechanical vibration or ultrasonic treatment of multilayer MXene to achieve MXene delamination. It is also found that the product obtained by F-ion etching can be embedded with an intercalant (application number 201810113395.4, a method for preparing two-dimensional layered MXene nanosheets), and then mechanically vibrated or ultrasonically treated in water to obtain single-layer or few-layer nanosheets. Various polar organic molecules, such as (hydrazine, isopropylamine, urea and dimethyl sulfoxide) or organic molecules (n-butylamine, choline hydroxide, tetrabutylammonium hydroxide), etc. can also be inserted into MXene to improve the stability of MXene and make up for the performance that multilayer MXene does not have. However, the MXene nanosheets prepared by these two preparation methods have defects, irregular shapes, and poor stability. Summary of the invention

[0004] In view of the problems of many defects, irregular shapes and poor stability of MXene nanosheets in the prior art, the purpose of the present invention is to provide a two-dimensional layered MXene nanosheet and a preparation method thereof. The method uses a multilayer MXene powder obtained by etching as a precursor, homogenizes it with a homogenizer and then uses a rapid annealing treatment. The method for preparing MXene nanosheets achieves the characteristics of uniform thickness, environmental protection, high efficiency and few defects.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing two-dimensional layered MXene nanosheets, the method comprising the following steps:

[0007] (1) MAX phase etching: MAX phase powder material is etched with hydrofluoric acid to etch away the main group elements in the MAX phase to obtain the etched MAX phase; the basic chemical formula of the MAX phase is expressed as M (n+1) AX n , M represents transition metal elements, A represents main group elements, and X represents carbon or nitrogen, such as Ti3SiC2 and Ti3AlC2.

[0008] (2) Etching the MAX phase, centrifuging and drying to obtain accordion-shaped multilayer MXene powder;

[0009] (3) Homogenization: Multilayer MXene powder is used as a precursor and homogenized using a homogenizer to open the MXene layers and reduce the size of MXene particles.

[0010] (4) Rapid annealing treatment: The powder obtained after the homogenization treatment in step (3) is subjected to rapid annealing treatment to remove the surface functional groups of MXene and obtain MXene nanosheets with regular structure and few defects.

[0011] Furthermore, in step (1), the weight ratio of the MAX phase powder material to hydrofluoric acid is 1:(4-6), and the concentration of hydrofluoric acid is 40-55wt.%.

[0012] Furthermore, during the etching process of step (1), the MAX phase powder material is slowly added in batches into a polytetrafluoroethylene beaker containing an etching liquid hydrofluoric acid, and the beaker is placed in a magnetic stirring water bath and stirred at 40° C.-50° C. for 1.5-3 h.

[0013] Furthermore, in step (2), the centrifugal treatment is to repeatedly centrifuge and wash the etched MAX phase until the solution is neutral, collect the precipitate and vacuum dry it to obtain a multilayer MXene powder.

[0014] Furthermore, the repeated centrifugation and washing process in step (2) is as follows: first, the rotation speed is controlled to be 4500-5500 rpm, the centrifugation time is 4-6 min, the supernatant is removed after centrifugation, and deionized water is added and fully shaken to redisperse the precipitate, and the centrifugation is performed again at a rotation speed of 4500-5500 rpm for 4-6 min. This process is repeated 10-15 times to remove the by-products of the etching reaction and dilute the acid solution until the pH of the solution is neutral (pH=7). Finally, the mixture after centrifugation is filtered out with a vacuum filtration pump to remove the precipitate for drying; the drying process is to place the precipitate in a vacuum oven at 40-60°C for 24 hours.

[0015] Furthermore, the homogenization process of step (3) is as follows: dispersing the multilayer MXene powder in anhydrous ethanol to obtain a suspension; adding the suspension to a homogenizer to start a circulation treatment, after the homogenization is completed, taking out the suspension and letting it stand for 1 hour, after pouring out the supernatant, the obtained precipitate is centrifuged, washed and freeze-dried to obtain a freeze-dried powder.

[0016] Furthermore, during the homogenization process of step (3), the ratio of the multilayer MXene powder to the anhydrous ethanol is (1-2) g: (40-80) ml; after the multilayer MXene powder is mixed with the anhydrous ethanol, it is stirred evenly with a glass rod to disperse the MXene powder in the anhydrous ethanol to form a suspension; the homogenization pressure is set to 180-1200 bar, and the homogenization time is 15-25 min; the precipitate is centrifuged and washed 3-5 times to remove the anhydrous ethanol; freeze drying is placed in a freeze dryer and freeze dried at a temperature of -45 to -35 ° C and a vacuum degree of more than 2 Pa.

[0017] Furthermore, during the centrifugal washing in step (3), the centrifugal speed is controlled to be 4500-5500 rpm, the supernatant is removed after centrifugation, and deionized water is added and shaken sufficiently to disperse the precipitate, and centrifuged again, and this is repeated 3-5 times to remove excess anhydrous ethanol.

[0018] Furthermore, the rapid annealing process in step (4) is as follows: placing the powder obtained in step (3) in a tubular furnace, heating the temperature to 700-750°C at a heating rate of 8-12°C / min under Ar atmosphere protection, and keeping the temperature for 28-30 minutes; after annealing, the obtained MXene nanosheets are sealed and refrigerated for storage.

[0019] The two-dimensional layered MXene nanosheets prepared by the method of the present invention have the characteristics of uniform thickness, high stability, regular shape and few defects.

[0020] Compared with the prior art, the design mechanism and beneficial effects of the present invention are as follows:

[0021] 1. Currently, the MXene nanosheets obtained by wet etching have abundant functional groups (-OH, -F, etc.) on their surfaces, which are defective and unstable. The method of the present invention uses the multilayer MXene structure obtained by etching as a precursor, uses a homogenizer to homogenize the MXene to achieve the purpose of opening the MXene layer and reducing the size of the MXene particles, and then uses rapid annealing treatment to effectively remove the functional groups on the MXene surface by rapid heating to obtain MXene nanosheets.

[0022] 2. The method of the present invention opens the MXene interlayer through homogenization treatment and then performs rapid annealing to remove the functional groups such as -O, -OH, and -F on the surface. This method effectively avoids the oxidation problem of MXene and realizes feasible preparation with uniform thickness, environmental protection, high efficiency, and few defects.

[0023] 3. The preparation method of the present invention omits the steps of conventional intercalation and ultrasonic stripping, and can effectively strip off multiple layers of Ti3C2Tx during the etching process. The obtained two-dimensional MXene nanosheets have more regular shapes and fewer defects, and the stability of MXene is improved.

[0024] 4. The preparation method of the present invention has the advantage of replacing the organic reagent intercalation preparation method and becoming the mainstream preparation method for MXene nanosheets. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the SEM morphology of the MAX phase;

[0026] Figure 2 This is the SEM morphology of the accordion-shaped multilayer MXene powder prepared in Example 1;

[0027] Figure 3 This is a SEM morphology of the nanosheets obtained after homogenization of the multilayer MXene powder prepared in Example 1;

[0028] Figure 4 XRD patterns of the MXene nanosheets prepared in Example 1 before and after annealing. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is described in detail below in conjunction with embodiments. The specific embodiments described herein are intended to explain the present invention, but are not intended to limit the present invention.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0031] In the following cases, KS-1800L high pressure homogenizer is used for homogenization.

[0032] Embodiment 1:

[0033] This embodiment provides a two-dimensional layered MXene nanosheet and a preparation method thereof, and the preparation process is as follows:

[0034] 1. Preparation of accordion-shaped multilayer MXene powder: Weigh 20 g of MAX phase Ti3AlC2 powder, slowly add 100 g of 50 wt.% hydrofluoric acid in batches, stir at 45 °C for 2 h, and etch away the Al element to obtain the etched MAX phase.

[0035] The obtained etching product is repeatedly centrifuged and washed for 10-15 times until the pH is 7, and the obtained mixture is filtered with a vacuum filtration pump, and the precipitate is collected and vacuum dried. Specifically, the repeated centrifugation and washing method is: first control the speed to 5000rpm, the time is 5min, remove the supernatant after centrifugation, add deionized water and shake it thoroughly to re-disperse the precipitate, centrifuge it again at 5000rpm for 5min, and repeat the washing 10-15 times to remove the by-products of the etching reaction and dilute the acid solution until the pH value of the solution is neutral; the precipitate obtained after centrifugation is placed in a vacuum oven and dried at 50°C for 12h to obtain a multilayer MXene powder (Ti3C2Tx) with an accordion-like structure.

[0036] 2. Preparation of MXene nanosheets: 10 g of multilayer MXene powder was dispersed in a beaker containing 400 ml of anhydrous ethanol, and stirred evenly with a glass rod to disperse the MXene into a suspension in the beaker. The high-pressure homogenizer was started and the homogenization pressure was set to 600 bar and the time was 20 min. The suspension was added to the homogenizer to start circulation. After the homogenization was completed, the homogenized product (a mixture of MXene and anhydrous ethanol) was taken out and allowed to stand for 1 hour. After the supernatant was poured out, it was centrifuged and washed 3-5 times until the pH value was 7, and then placed in a freeze dryer at -40 ° C and a vacuum degree of more than 2 Pa for freeze drying to obtain a freeze-dried powder; wherein: during centrifugal washing, the centrifugal speed was controlled to 5000 rpm, the supernatant was removed after centrifugation, and deionized water was added to shake and oscillate sufficiently to disperse the precipitate, and centrifuged again. This was repeated 4 times to remove excess anhydrous ethanol.

[0037] 3. Rapid annealing treatment: The freeze-dried powder was placed in a tubular furnace and rapidly heated to 750°C at a heating rate of 10°C / min under Ar atmosphere protection, and then kept warm for 30 minutes; after annealing, the obtained MXene nanosheets were sealed and refrigerated for storage.

[0038] Embodiment 2:

[0039] This embodiment provides a two-dimensional layered material MXene nanosheet and a preparation method, and the preparation process is as follows:

[0040] 1. Preparation of accordion-shaped multilayer MXene powder: Weigh 20 g of MAX phase Ti3AlC2 powder, slowly add 100 g of 50 wt.% hydrofluoric acid in batches, stir at 50 °C for 2 h, and etch away the Al element to obtain the etched MAX phase.

[0041] The obtained etching product was repeatedly centrifuged and washed for 10-15 times until pH = 7, and the obtained mixture was filtered with a vacuum filtration pump, and the precipitate was collected and vacuum dried. Specifically, the repeated centrifugation and washing method is: first control the speed to 5000rpm, the time is 5min, remove the supernatant after centrifugation, add deionized water and shake it thoroughly to re-disperse the precipitate, and then centrifuge it at 5000rpm for 5min, repeat this 10-15 times to remove the by-products of the etching reaction and dilute the acid solution until the pH value of the solution is neutral; the precipitate obtained after centrifugation is placed in a vacuum oven and dried at 50°C for 12h to obtain an accordion-shaped multilayer MXene powder (Ti3C2Tx).

[0042] 2. Preparation of MXene nanosheets: 10 g of multilayer MXene powder was dispersed in a beaker containing 400 ml of anhydrous ethanol, and stirred evenly with a glass rod to disperse the MXene into a suspension in the beaker. The equipment was started and the homogenization pressure was set to 800 bar for 20 min, and the suspension was added to the homogenizer to start circulation. After the homogenization was completed, the homogenized product (a mixture of MXene and anhydrous ethanol) was taken out and allowed to stand for 1 h. After the supernatant was poured out, it was centrifuged and washed 3-5 times until the pH value was 7, and then placed in a freeze dryer for freeze drying at -42 ° C and a vacuum degree of more than 2 Pa to obtain a freeze-dried powder; wherein: during centrifugal washing, the centrifugal speed was controlled to 5000 rpm, the supernatant was removed after centrifugation, and deionized water was added to shake and oscillate sufficiently to disperse the precipitate, and centrifuged again, and this was repeated 4 times to remove excess anhydrous ethanol.

[0043] 3. Rapid annealing treatment: The freeze-dried powder was placed in a tubular furnace and rapidly heated to 750°C at a heating rate of 10°C / min under Ar atmosphere protection, and then kept warm for 30 minutes; after annealing, the obtained MXene nanosheets were sealed and refrigerated for storage.

[0044] Embodiment 3:

[0045] This embodiment provides a two-dimensional layered material MXene nanosheet and a preparation method, and the preparation process is as follows:

[0046] 1. Preparation of accordion-shaped multilayer MXene powder: Weigh 20 g of MAX phase Ti3AlC2 powder, slowly add a total of 100 g of 50 wt.% concentration in batches, stir at 50 °C for 2 h, and etch away the Al element to obtain the etched MAX phase.

[0047] The obtained etching product is repeatedly centrifuged and washed for 10-15 times until pH = 7, and the obtained mixture is filtered with a vacuum filtration pump, and the precipitate is collected and vacuum dried. Specifically, the repeated centrifugation and washing method is: first control the speed to 5000rpm, the time is 5min, remove the supernatant after centrifugation, add deionized water and shake it thoroughly to re-disperse the precipitate, centrifuge it again at 5000rpm for 5min, repeat this 10-15 times to remove the by-products of the etching reaction and dilute the acid solution until the pH value of the solution is neutral; the precipitate obtained after centrifugation is placed in a vacuum oven and dried at 50°C for 12h to obtain an accordion-shaped multilayer MXene powder (Ti3C2Tx).

[0048] 2. Preparation of MXene nanosheets: 10 g of multilayer MXene powder was dispersed in a 400 ml beaker filled with anhydrous ethanol, and stirred evenly with a glass rod to disperse the MXene into a suspension in the beaker. The high-pressure homogenizer was started and the homogenization pressure was set to 1100 bar and the time was 20 min. The suspension was added to the homogenizer to start circulation. After the homogenization was completed, the homogenized product (a mixture of MXene and anhydrous ethanol) was taken out and allowed to stand for 1 hour. After the supernatant was poured out, it was centrifuged and washed 3-5 times until the pH value was 7, and then placed in a freeze dryer at -40 ° C and a vacuum degree of more than 2 Pa for freeze drying to obtain a freeze-dried powder; wherein: during centrifugal washing, the centrifugal speed was controlled to 5000 rpm, the supernatant was removed after centrifugation, and deionized water was added to shake and oscillate sufficiently to disperse the precipitate, and centrifuged again. This was repeated 4 times to remove excess anhydrous ethanol.

[0049] 3. Rapid annealing heat treatment: The freeze-dried powder was placed in a tubular furnace and rapidly heated to 720°C at a heating rate of 10°C / min under Ar atmosphere protection, and then kept warm for 30 minutes; after annealing, the obtained MXene nanosheets were sealed and refrigerated for storage.

[0050] Embodiment 4:

[0051] This embodiment provides a two-dimensional layered material MXene nanosheet and a preparation method, and the preparation process is as follows:

[0052] 1. Preparation of accordion-shaped multilayer MXene powder: Weigh 20 g of MAX phase Ti3AlC2 powder, slowly add 100 g of 50 wt.% hydrofluoric acid in batches, stir at 45 °C for 2 h, and etch away the Al element to obtain the etched MAX phase.

[0053] The obtained etching product was repeatedly centrifuged and washed for 10-15 times until the pH was 7, and the obtained mixture was filtered with a vacuum filtration pump, and the precipitate was collected and vacuum dried. Specifically, the repeated centrifugation and washing method is as follows: first, the speed is controlled to 5000rpm, the time is 5min, the supernatant is removed after centrifugation, and then deionized water is added to shake and oscillate sufficiently to redisperse the precipitate, and centrifuge again, and this is repeated 10-15 times to remove the by-products of the etching reaction and dilute the acid solution until the pH value of the solution is neutral; the precipitate obtained after centrifugation is placed in a vacuum oven and dried at 50°C for 12h to obtain an accordion-shaped multilayer MXene powder (Ti3C2Tx).

[0054] 2. Preparation of MXene nanosheets: 10 g of multilayer MXene powder was dispersed in a beaker containing 400 ml of anhydrous ethanol, and stirred evenly with a glass rod to disperse the MXene into a suspension in the beaker. The high-pressure homogenizer was started and the homogenization pressure was set to 1200 bar and the time was 20 min. The suspension was added to the homogenizer to start circulation. After the homogenization was completed, the homogenized product (a mixture of MXene and anhydrous ethanol) was taken out and allowed to stand for 1 hour. After the supernatant was poured out, it was centrifuged and washed 3-5 times until pH = 7, and placed in a freeze dryer at -40 ° C and a vacuum degree of more than 2 Pa for freeze drying to obtain a freeze-dried powder; wherein: during centrifugal washing, the centrifugal speed was controlled to 5000 rpm, the supernatant was removed after centrifugation, and deionized water was added to shake and oscillate sufficiently to disperse the precipitate, and centrifuged again. This was repeated 4 times to remove excess anhydrous ethanol.

[0055] 3. Rapid annealing treatment: The freeze-dried powder was placed in a tubular furnace and rapidly heated to 720°C at a heating rate of 10°C / min under Ar atmosphere protection, and then kept warm for 28 minutes; after annealing, the obtained MXene was sealed and refrigerated for storage.

[0056] Comparative Example 1:

[0057] This example provides a two-dimensional layered material MXene nanosheet and a preparation method, and the preparation process is as follows:

[0058] 1. Preparation of accordion-shaped multilayer MXene powder: Weigh 20 g of MAX phase Ti3AlC2 powder, slowly add 100 g of 50 wt.% hydrofluoric acid in batches, stir at 45 °C for 2 h, and etch away the Al element to obtain the etched MAX phase.

[0059] The obtained etching product was repeatedly centrifuged and washed for 10-15 times until pH = 7, and the obtained mixture was filtered with a vacuum filtration pump, and the precipitate was collected and vacuum dried. Specifically, the repeated centrifugal washing method is: first control the speed to 5000rpm, the time is 5min, remove the supernatant after centrifugation, add deionized water and shake it thoroughly to re-disperse the precipitate, centrifuge it again at 5000rpm for 5min, and repeat the washing 10-15 times to remove the by-products of the etching reaction and dilute the acid solution until the pH value of the solution is neutral; the precipitate obtained after centrifugation is placed in a vacuum oven and dried at 50°C for 12h to obtain an accordion-shaped multilayer MXene powder (Ti3C2Tx).

[0060] 2. Preparation of MXene nanosheets: Take 10g of multilayer MXene powder and disperse it in a beaker filled with 400ml of anhydrous ethanol. Stir it evenly with a glass rod to disperse the MXene into a suspension in the beaker. Start the high-pressure homogenizer and set the homogenization pressure to 200bar and the time to 20min. Add the suspension into the homogenizer and start circulation. After the homogenization is completed, take out the homogenized product (a mixture of MXene and anhydrous ethanol) and let it stand for 1h. After pouring out the supernatant, centrifuge and wash it 3-5 times until the pH is 7, and put it into a freeze dryer and freeze-dry it at -40℃ and a vacuum degree of more than 2Pa to obtain a freeze-dried powder.

[0061] 3. Rapid annealing treatment: The freeze-dried powder was placed in a tubular furnace and rapidly heated to 750°C at a heating rate of 10°C / min under Ar atmosphere protection, and then kept warm for 30 minutes; after annealing, the obtained MXene nanosheets were sealed and refrigerated for storage.

[0062] Comparative Example 2:

[0063] This example provides a two-dimensional layered material MXene nanosheet and a preparation method, and the preparation process is as follows:

[0064] 1. Preparation of accordion-shaped multilayer MXene powder: Weigh 20 g of MAX phase Ti3AlC2 powder, slowly add 100 g of 50 wt.% hydrofluoric acid in batches, stir at 50 °C for 2 h, and etch away the Al element to obtain the etched MAX phase.

[0065] The obtained etching product was repeatedly centrifuged and washed for 10-15 times until pH = 7, and the obtained mixture was filtered with a vacuum filtration pump, and the precipitate was collected and vacuum dried. Specifically, the repeated centrifugal washing method is: first control the speed to 5000rpm, the time is 5min, remove the supernatant after centrifugation, add deionized water and shake it thoroughly to re-disperse the precipitate, centrifuge it again at 5000rpm for 5min, and repeat the washing 10-15 times to remove the by-products of the etching reaction and dilute the acid solution until the pH value of the solution is neutral; the precipitate obtained after centrifugation is placed in a vacuum oven and dried at 50°C for 12h to obtain an accordion-shaped multilayer MXene powder (Ti3C2Tx).

[0066] 2. Preparation of MXene nanosheets: 10 g of multilayer MXene powder was dispersed in a beaker containing 400 ml of anhydrous ethanol, and stirred evenly with a glass rod to disperse the MXene into a suspension in the beaker. The high-pressure homogenizer was started and the homogenization pressure was set to 400 bar and the time was 20 min. The suspension was added to the homogenizer to start circulation. After the homogenization was completed, the homogenized product (a mixture of MXene and anhydrous ethanol) was taken out and allowed to stand for 1 hour. After the supernatant was poured out, it was centrifuged and washed 3-5 times until the pH value was 7, and then placed in a freeze dryer at -40 ° C and a vacuum degree of more than 2 Pa for freeze drying to obtain a freeze-dried powder; wherein: during centrifugal washing, the centrifugal speed was controlled to 5000 rpm, the supernatant was removed after centrifugation, and deionized water was added to shake and oscillate sufficiently to disperse the precipitate, and centrifuged again. This was repeated 4 times to remove excess anhydrous ethanol.

[0067] 3. Rapid annealing treatment: The freeze-dried powder was placed in a tubular furnace and rapidly heated to 720°C at a heating rate of 10°C / min under Ar atmosphere protection, and then kept warm for 30 minutes; after annealing, the obtained MXene nanosheets were sealed and refrigerated for storage.

[0068] Figure 1 This is a scanning electron microscope image of the MAX phase Ti3AlC2 powder used in Example 1. The accordion-shaped multilayer MXene powder obtained after etching has a morphology as shown in FIG. Figure 2 , obvious multilayer MXene can be observed; then the SEM morphology of the nanosheets obtained after the multilayer MXene powder is homogenized is shown in Figure 3 , it can be observed that the MXene lateral size is 200 nm and the thickness is 1-2 nm; Figure 4The XRD diagram of MXene nanosheets before and after annealing. The XRD test results show that the MXene diffraction peak angles change from 8.649°, 17.974°, 27.499° and 34.084° before annealing to 8.983°, 18.208°, 27.633° and 35.187° after annealing, respectively. It can be found that the MXene diffraction peaks have left shifts at different angles after annealing, indicating that annealing treatment has a positive effect on the removal of functional groups such as -O, -OH, and -F between MXene layers.

[0069] Table 1 lists the changes in the ratio of F to Ti, O to Ti on the surface and between layers of MXene before and after annealing. It can be seen that the ratio of O, F and Ti elements decreases after annealing, and the amount of F and O elements removed from the MXene surface is greater. This shows that annealing of MXene nanosheets after specific homogenization can significantly remove the surface and interlayer -O, -F and other functional groups, and reduce the content of O and F elements.

[0070] Table 1

[0071]

[0072] Table 2 shows the homogenization pressure applied in the above embodiments and comparative examples and the size of the obtained MXene nanosheets. It can be seen from Table 2 that when the homogenization pressure is 600-1200 bar, the prepared MXene nanosheets have a lateral size of 0.1-1 μm and a thickness of 1-2 nm, and are dimensionally stable.

[0073] Table 2 MXene size

[0074]

[0075]

[0076] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A method for preparing two-dimensional layered MXene nanosheets, characterized in that: The method comprises the following steps: (1) MAX phase etching: MAX phase powder material is etched using hydrofluoric acid to etch away the main group elements in the MAX phase to obtain an etched MAX phase; (2) etching the MAX phase and obtaining multilayer MXene powder after centrifugation and drying; (3) Homogenization: Multilayer MXene powder is used as a precursor and homogenized using a homogenizer to open the MXene layers and reduce the size of MXene particles. (4) Rapid annealing treatment: The powder obtained after the treatment in step (3) is subjected to rapid annealing treatment to remove the surface functional groups of MXene and obtain MXene nanosheets with regular structure and few defects.

2. The method for preparing two-dimensional layered MXene nanosheets according to claim 1, characterized in that: In step (1), the weight ratio of the MAX phase powder material to hydrofluoric acid is 1:(4-6), and the concentration of hydrofluoric acid is 40-55wt.%.

3. The method for preparing a two-dimensional layered MXene nanosheet according to claim 1 or 2, characterized in that: During the etching process of step (1), the MAX phase powder material is slowly added in batches into a polytetrafluoroethylene beaker containing an etching liquid hydrofluoric acid, and the beaker is placed in a magnetic stirring water bath and stirred at 40-50° C. for 1.5-3 h.

4. The method for preparing two-dimensional layered MXene nanosheets according to claim 1, characterized in that: In step (2), the centrifugal treatment is to repeatedly centrifuge and wash the etched MAX phase until the solution is neutral, collect the precipitate and vacuum dry it to obtain a multilayer MXene powder.

5. The method for preparing a two-dimensional layered MXene nanosheet according to claim 1 or 4, characterized in that: The repeated centrifugation and washing process of step (2) is as follows: first, the rotation speed is controlled to be 4500-5500 rpm, the supernatant is removed after centrifugation, deionized water is added and the mixture is fully shaken to redisperse the precipitate, and the mixture is centrifuged again. This process is repeated 10-15 times to remove the byproducts of the etching reaction and dilute the acid solution until the pH of the solution is neutral. Finally, the mixture after centrifugation is filtered out with a vacuum filtration pump to remove the precipitate and dry it; Drying The precipitate was placed in a vacuum oven at 40-60°C for drying.

6. The method for preparing two-dimensional layered MXene nanosheets according to claim 1, characterized in that: The homogenization process of step (3) is as follows: the multilayer MXene powder is dispersed in anhydrous ethanol to obtain a suspension; the suspension is added to a homogenizer to start a circulation treatment. After the homogenization is completed, the suspension is taken out and allowed to stand for 1 hour, the supernatant is poured out, and the obtained precipitate is centrifuged, washed and freeze-dried to obtain a freeze-dried powder.

7. The method for preparing two-dimensional layered MXene nanosheets according to claim 6, characterized in that: During the homogenization process of step (3), the ratio of multilayer MXene powder to anhydrous ethanol is (1-2) g: (40-80) ml; after the multilayer MXene powder is mixed with anhydrous ethanol, it is stirred evenly with a glass rod to disperse the MXene powder in the anhydrous ethanol to form a suspension; the homogenization pressure is set to 180-1200 bar, and the homogenization time is 15-25 min; the precipitate is centrifuged and washed 3-5 times to remove the anhydrous ethanol; freeze drying is placed in a freeze dryer and freeze dried at a temperature of -45 to -35 ° C and a vacuum degree of more than 2 Pa.

8. The method for preparing two-dimensional layered MXene nanosheets according to claim 7, characterized in that: During the centrifugal washing in step (3), the centrifugal speed is controlled to be 4500-5500 rpm. After centrifugation, the supernatant is removed, and deionized water is added and shaken sufficiently to disperse the precipitate. Centrifugation is performed again, and this process is repeated 3-5 times to remove excess anhydrous ethanol.

9. The method for preparing two-dimensional layered MXene nanosheets according to claim 7, characterized in that: The rapid annealing process in step (4) is as follows: placing the powder obtained in step (3) in a tubular furnace, heating the temperature to 700-750°C at a heating rate of 8-12°C / min under Ar atmosphere protection, and keeping the temperature for 28-30 minutes; after annealing, the obtained MXene nanosheets are sealed and refrigerated for storage.

10. A two-dimensional layered MXene nanosheet prepared by the method of claim 1, characterized in that: The MXene nanosheets have the characteristics of uniform thickness, high stability, regular shape and few defects.

Citation Information

Patent Citations

  • A method for preparing two-dimensional layered MXene nanosheets

    CN108298541B

Cited By

  • Difunctional flexible MXene film and preparation method thereof

    CN121342030A

  • Co-intercalation MXene in-situ synergistic growth CNTs / SiOx composite material and preparation method and application thereof

    CN121546005A